Gait Variability Patterns are Altered in Healthy Young Individuals During the Acute Reperfusion Phase of Ischemia-Reperfusion - Myers, Sara A.; Stergiou, Nick; Pipinos, Iraklis I.; Johanning, Jason M. (The Journal of surgical research, 2010)
The role of ischemia reperfusion contributing to functional impairment in lower extremity peripheral arterial disease (PAD) patients has not previously been elucidated. The evaluation of gait variability patterns has proven useful in many pathologic populations. Therefore, the purpose of this study is to isolate and determine the specific effect of the acute reperfusion phase of ischemia-reperfusion on gait variability in young individuals with no vascular disease. Thirty healthy young individuals walked on a treadmill during baseline and the acute reperfusion phase of ischemia-reperfusion conditions while lower extremity joint kinematics were captured. Stride to stride variability was assessed using the largest Lyapunov exponent, approximate entropy, standard deviation, and coefficient of variation. Differences in gait variability between conditions were assessed using dependent t-tests. The largest Lyapunov exponent values and approximate entropy values were significantly higher in the acute reperfusion phase of ischemia-reperfusion condition for the ankle, knee, and the hip. Coefficient of variation was significantly higher at the hip and standard deviation was higher at the knee and the hip during the acute reperfusion phase of ischemia-reperfusion condition. The acute reperfusion phase of the ischemia-reperfusion cycle alters gait variability patterns at the ankle, knee, and the hip in healthy young individuals. Our findings indicate increased noise and irregularity of gait variability patterns post-ischemia. In young healthy individuals who do not have neuromuscular impairments, significant gait alterations are present during walking after a period of interruption of blood flow.